Lumbar puncture in patients with neurologic conditions - Babapour Mofrad, Rosha (Alzheimers Dement (Amst), 2017)
A lumbar puncture (LP) is performed to obtain cerebrospinal fluid. It is implemented in the clinic on a routine basis to aid the diagnosis of neurologic diseases. This paper accompanies an informative lumbar puncture video that shows the lumbar puncture procedure as routinely performed in the VUmc Alzheimer center based on the consensus guidelines by Engelborghs et al.